2017
DOI: 10.2224/sbp.5896
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Machiavellian ethical leadership and employee power distance on employee voice

Abstract: We investigated how employees respond to Machiavellian supervisors exerting ethical leadership. Participants were 252 matched supervisor–employee dyads, and we administered measures of supervisor ethical leadership, employee voice, employee power distance orientation, and supervisor Machiavellianism. Results revealed that Machiavellian supervisors' ethical leader behaviors were perceived to be genuine by subordinate employees, and that ethical leadership promoted supervisors' extrarole voice behaviors. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…In addition to the 37 publications mentioned above, two studies (Kalshoven et al, ; Kwak & Shim, ) used adaptations of Brown et al's () Ethical Leadership Scale (ELS): a 38‐item Ethical Leadership at Work questionnaire developed and validated in the Netherlands by Kalshoven et al () and a 10‐item scale developed by Den Hartog and Belschak ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the 37 publications mentioned above, two studies (Kalshoven et al, ; Kwak & Shim, ) used adaptations of Brown et al's () Ethical Leadership Scale (ELS): a 38‐item Ethical Leadership at Work questionnaire developed and validated in the Netherlands by Kalshoven et al () and a 10‐item scale developed by Den Hartog and Belschak ().…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies examine the influence on the strength of the relationship between EL and OCBs of different moderation variables: Climate strength (Shin, ), Emphatic concern and Moral awareness (Kalshoven et al, ), Workplace friendships and Traditionality (Liu, Kwan, Fu, & Mao, ), Organizational change and involvement in change (Sharif & Scandura, ), Perceptions of politics and Gender (Kacmar et al, ), Personal control (Hassan, ), and Machiavellianism (Kwak & Shim, ), all influencing the effects of EL on OCBs.…”
Section: Main Findings Of the Studiesmentioning
confidence: 99%
“…This opinion is being widely adopted. It has been shown that as an extra-role behavior, voice behavior is closely related to power distance [44,45]. Leaders with a high power distance orientation tend to maintain their authority in an autocratic way, rarely communicating with employees or accepting their suggestions [61].…”
Section: Voice Behavior As a Mediatormentioning
confidence: 99%
“…As innovation behavior must effectively gather individual wisdom and integrate different perspectives, it requires individuals to voice [42]. As a kind of extra-role behavior, voice behavior refers to the constructive suggestions regarding organizational development based on individual observations and understanding about the organization [43], which is often affected by organizational power distance [44,45]. Therefore, power distance may influence individual innovation behavior based on the mediating effect of voice behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Within types of leadership, Machiavellianism is regarded as one of leadership styles that is not parallel with the ethics (Brown and Treviño, 2006, p.604). A manager, who is committing fraud and prioritizing its interests rather than the organization and subordinates by exhibiting the forms of Machiavellian behaviors, will not be effective when it has directed its subordinates at the point of ethical values and organizational goals (Kwak andShim, 2017, p.1489).…”
Section: Machiavellianismmentioning
confidence: 99%